Educational actions for the elderly in public Higher Education institutions in the state of Paraná (Práxis Educativa, 2019)
This research is qualitative, based on materialist dialectic. The aim is to analyze the educational actions for the elderly developed by projects/courses in public Institutions of Higher Education from Paraná state, Brazil, as strategies for the political emancipation of the elderly, founded on the concept of lifelong education, drawn from Konder (2009), Marx (2009), Mészáros (2006) and Oliveira (1998). For data collection, questionnaires were applied to 146 elderly people of the Open University for the Third Age of the public institutions of Higher Education from Paraná. Questionnaires were also applied to 25 teachers. As a result, the research shows that the educational activities for the elderly aim emancipatory processes, even though they have no such name on their goals. Even with limitations, education for the elderly age contributes to the awareness of the elderly, being able to glimpse political emancipation from the dialectical relationship between education, man and society. Keywords: Emancipation policy. Permanent Education. Open University for the Third Age.